Trust, regulation and trade - Rudiger Von Arnim; Bernhard Tröster; Werner Raza (Hans-Böckler-Stiftung, 2024)
Can consumers trust that the food they buy in the supermarket, even if imported, is not harmful to their health? What would be the consequences if their trust in existing health and safety standards were to be undermined by recognizing lower foreign standards? Against the backdrop of public debates (e.g., on the merits of chlorine-washed chicken, banned in the EU, but legal under the proposed TTIP agreement with the United States), this paper discusses the close link between trust, regulation and international trade. It turns out that as local regulatory systems have evolved, they have created a "generalized trust" that promotes economic activity. Aggressive regulatory harmonization through trade agreements could jeopardize the fragile balance of trust and activity.
Keywords: 330; non-tariff barriers; TTIP; CETA; international treaties; trade agreement